Mitigasi dan Penanganan Penyebaran Virus Covid-19 kepada Perangkat Desa dan Tokoh Masyarakat - Abdurrachman Abdurrachman; Umi Hanifah; Isy Annisa; Dwi Bagus Pambudi (LPPM Akbid Harapan Ibu Pekalongan, 2022)
The number of Covid-19 cases continues to grow and spreads to all parts of the world rapidly. So far, 65 countries have been infected with this virus. The Indonesian government is trying to tackle this epidemic with various policies in various sectors. One of the policies set by the government to break the chain of this virus is the social distancing policy, namely by limiting activities outside the house to reduce interactions between humans so that it can reduce the possibility of Covid-19 transmission in Indonesia. The social distancing policy encountered several obstacles because humans never stopped their mobility and moving activities from one place to another. Therefore, the successful implementation of this policy requires the involvement of stakeholders in a democratic and participatory manner. The regional government is trying to prevent the spread of the Covid-19 virus by setting up Covid-19 control posts at several points that allow the arrival of residents from outside the city, such as at terminals, sub-districts and bus stops. This aims to educate the community and village officials in preventing additional cases in areas that have not been affected by Covid-19. Based on the results of the pre and posttest that has been carried out by the community, residents can find out the latest conditions so that residents can make efforts to handle and prevent health problems during the Covid-19 pandemic quickly and accurately.